Role of reptiles and associated arthropods in the epidemiology of rickettsioses: A one health paradigm. - Jairo Alfonso Mendoza-Roldan; Ranju Ravindran Santhakumari Manoj; Maria Stefania Latrofa; Roberta Iatta; Giada Annoscia; Piero Lovreglio; Angela Stufano; Filipe Dantas-Torres; Bernard Davoust; Younes Laidoudi; Oleg Mediannikov; Domenico Otranto (Public Library of Science (PLoS), 2021)
We assessed the presence of Rickettsia spp., Coxiella burnetii and Anaplasma phagocytophilum in reptiles, their ectoparasites and in questing ticks collected in a nature preserve park in southern Italy, as well as in a peri-urban area in another region. We also investigated the exposure to these pathogens in forestry workers, farmers and livestock breeders living or working in the nature preserve park given the report of anecdotal cases of spotted fever rickettsioses. Rickettsia spp. were molecularly detected in Podarcis muralis and Podarcis siculus lizards (i.e., 3.1%), in Ixodes ricinus (up to 87.5%) and in Neotrombicula autumnalis (up to 8.3%) collected from them as well as in I. ricinus collected from the environment (up to 28.4%). Rickettsia monacensis was the most prevalent species followed by Rickettsia helvetica. An undescribed member of the family Anaplasmataceae was detected in 2.4% and 0.8% of the reptiles and ectoparasites, respectively. Sera from human subjects (n = 50) were serologically screened and antibodies to Rickettsia spp. (n = 4; 8%), C. burnetti (n = 8; 16%) and A. phagocytophilum (n = 11; 22%) were detected. Two ticks collected from two forestry workers were positive for spotted fever group (SFG) rickettsiae. Ixodes ricinus is involved in the transmission of SFG rickettsiae (R. monacensis and R. helvetica) in southern Europe and lizards could play a role in the sylvatic cycle of R. monacensis, as amplifying hosts. Meanwhile, N. autumnalis could be involved in the enzootic cycle of some SFG rickettsiae among these animals. People living or working in the southern Italian nature preserve park investigated are exposed to SFG rickettsiae, C. burnetii and A. phagocytophilum.